2015
DOI: 10.1111/1468-5973.12094
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Adaptation in Multi‐Stakeholder Crisis Response: An Experimental Study

Abstract: Modern day crises demand organizations to collaborate and adapt to new roles, functions and structures. In such situations, lack of collaborative behaviour and openness between organizations can result in reduced adaptive ability.Therefore, it is important to facilitate collaboration between organizations.We have studied the extent to which crisis managers are prepared to work with personnel and resources from organizations other than their own when responding to crises. An experiment was designed with four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 75 publications
(98 reference statements)
0
27
0
Order By: Relevance
“…Ekman (2012) found that when it came to trusting, professional familiarity across boundaries was more important than cultural perspectives. Ekman's findings were confirmed by Pramanik et al (2015), who found in a Swedish experimental collaboration study that there was a strong group bias among participants and that these partakers tended to more easily trust members of organizations that they knew beforehand and with whom could readily identify. Group bias has also been found during exercise planning processes, and this has resulted in unnecessary ad hoc processes and sector-specific exercisescript development (Paton et al 1998).…”
Section: Collaboration Exercise Usefulnessmentioning
confidence: 79%
“…Ekman (2012) found that when it came to trusting, professional familiarity across boundaries was more important than cultural perspectives. Ekman's findings were confirmed by Pramanik et al (2015), who found in a Swedish experimental collaboration study that there was a strong group bias among participants and that these partakers tended to more easily trust members of organizations that they knew beforehand and with whom could readily identify. Group bias has also been found during exercise planning processes, and this has resulted in unnecessary ad hoc processes and sector-specific exercisescript development (Paton et al 1998).…”
Section: Collaboration Exercise Usefulnessmentioning
confidence: 79%
“…Monopolizing, not sharing or showing a lack of interest in gaining new knowledge may be proven in extreme situations to be very dangerous (Lerbinger, 2012). Pramanik, Ekman, Hassel and Tehler (2015) emphasize the need to open cooperation with other organizations. Sharing the experience with others will help in coping with one's own crisis.…”
Section: Competencies Of a Crisis Managermentioning
confidence: 99%
“…Pramanik, et al [29] discovered a tendency of strong ingroup bias among exercise participants, and argued that participants found it easier to collaborate with, and trust, participants they could identify with based on, for example, similar educational background, professional experiences or type of uniform. To build trust across sectors, exercise designers have to focus on joint problem solving and variation during exercises, hence allowing for improvisation and the trying of new strategies contributes to enhance learning [30].…”
Section: Introductionmentioning
confidence: 99%